Financing Constraints of Nepalese Small and Medium Enterprises - Joshi, Shreya (Nepalese Journal of Management Science and Research, 2025)
The major objective of the study is to examine the financing constraints of Nepalese SMEs. The study’s specific goals are to examine respondents’ perceptions of bank lending technologies, firm characteristics, firm owner characteristics, SME financial information, loan characteristics, and loan access and repayment capacity. To determine the relationship between loan characteristics, loan repayment capacity, SME financial information, firm characteristics, firm owner characteristics, and bank lending technologies and loan access to loan. To find the most important factors influencing loan access for Nepalese SMEs and to examine the effects of loan characteristics, loan repayment capacity, SME financial information, firm characteristics, firm owner characteristics, and bank lending technologies.